Cortical spreading depolarisation-induced facial hyperalgesia, photophobia and hypomotility are ameliorated by sumatriptan and olcegepant - Tang, Chunhua (Sci Rep, 2020)
Cortical spreading depolarisation (CSD), the neural mechanism underlying migraine aura, may cause headache by sensitising the trigeminal system. Photophobia, the most bothersome accompanying symptom during migraine attacks, is more prevalent in migraine with aura than in migraine without aura. Whether CSD plays a role in developing photophobia remains unknown. Moreover, migraine-induced physical hypoactivity contributes to loss of productivity. We aimed to investigate the development of trigeminal sensitisation, photophobia and locomotive abnormality after KCl-induced CSD using 86 male C57BL/6 mice. Sham-operated mice were used as controls. We confirmed the presence of trigeminal sensitisation and photophobia at 24 h after CSD. CSD-subjected mice also exhibited significantly reduced locomotive activity in both light and dark zones. Hence, the CSD-induced hypomobility was likely to be independent of photophobia. The 5-HT(1B/1D) agonist, sumatriptan, corrected all these CSD-induced abnormalities. Moreover, dose dependency was demonstrated in the ameliorating effect of the calcitonin gene-related peptide (CGRP) receptor antagonist, olcegepant, on these abnormalities. Sumatriptan and olcegepant improved mouse locomotion with therapeutic lags ranging from 20 to 30 min. Collectively, CSD caused trigeminal sensitisation, photophobia and hypomobility that persisted for at least 24 h by a mechanism involving the 5-HT(1B/1D) and CGRP activity.